2021
DOI: 10.3390/diagnostics11091528
|View full text |Cite
|
Sign up to set email alerts
|

Trial Design of a Prospective Multicenter Diagnostic Accuracy Study of a Point-of-Care Test for the Detection of Taenia solium Taeniosis and Neurocysticercosis in Hospital-Based Settings in Tanzania

Abstract: Taenia solium diagnosis is challenging as trained personnel, good diagnostic tools, and infrastructure is lacking in resource-poor areas. This paper aims to describe the study trial design adopted to evaluate a newly developed rapid point-of-care test that simultaneously detects taeniosis and neurocysticercosis (TS POC) in three district hospitals in Tanzania. The two-stage design included three types of patients: patients with specific neurological signs and symptoms (group 1); patients with complaints compat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Further details on the project’s recruitment, study procedures and diagnostic criteria can be found elsewhere. [ 17 ]…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Further details on the project’s recruitment, study procedures and diagnostic criteria can be found elsewhere. [ 17 ]…”
Section: Methodsmentioning
confidence: 99%
“…For the second comparison, only serologically positive patients were chosen, because no serologically negative patients from the OPD received a CT scan as in accordance with the study protocol. [ 17 ] Last, we also compared clinical characteristics of PWE and NCC by stage of the lesions (at least one active stage lesions versus only calcified lesions).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a point-of-care test (POCT) was developed for the detection of T. solium taeniasis and NCC in hospital-based settings ( Trevisan et al, 2021 ; Mubanga et al, 2021 ). Their prototype lateral-flow assay kit consisted of two strips and used two kinds of recombinant proteins, rT24H and rES33.…”
Section: Introductionmentioning
confidence: 99%